The Blame Business : the Uses and Misuses of Accountability. - Fineman, Stephen (Reaktion Books, 2015)
Whenever anything goes wrong our first instinct is often to find someone to blame. Blame infuses our society in myriad ways, seeding rancor and revenge, dividing lovers, coworkers, communities, and nations. Yet blame, appropriately placed and managed, safeguards moral order and legal culpability. In this book, Stephen Fineman explores this duality inherent in blame, taking us on a fascinating journey across blame's sometimes bitter-sometimes just-landscape. Fineman focuses on blame's roots and enduring manifestations, from the witch hunts of the past to today's more buttoned-up scape.